Entre angústias e desafios de professores de estudantes com deficiência intelectual: uma possibilidade de alfabetização a partir da sequência didática - Grassi, Ronise Stela Molina (2023)
The research entitled “Between anxieties and challenges of students’ teachers with intellectual disabilities: a possibility of literacy from the didactic sequence” brings an analysis of how the literacy practices of teachers in Elementary School Final Years (6th to 9th) are configured, in the area of intellectual disability, in a state school within the scope of SRE Linhares-ES. The work investigates whether the didactic sequence focusing on literacy activities produced collectively by teachers, entailed to their daily practices, contributes to the learning of Special Education students, especially those with intellectual disabilities, enabling the advancement of their cognitive and social capabilities. Methodologically, to encourage theoretical discussions and support the analyses, the research is based on the historical-cultural perspective defended by Vigotski (1998, 2000, 2011 and 2012) and authors who discuss the field of disability anchored in this approach, such as Góes (2002) and Oliveira (1997). To deepen the discussions around Literacy and Language, in the research context, we sought theoretical support in Bakhtin (2004 and 2011); Geraldi (1984,1997 and 2010); Antunes (2003); Cagliari (2005) and researchers focusing on didactic sequence studies such as Dolz; Noverraz; Schneuwly (2004), Rojo (2013) and Zabala (1998). Based on the discussions generated by these theoretical contributions and the research field investigated, we verified that the didactic sequence is an alternative path to the literacy of the students with intellectual disabilities. It allows you to articulate reading and writing activities, with the text being the teaching object and the language understood from a verbal interaction perspective. On the other hand, we understand that, if thought with a greater focus on deciphering linguistic codes, it does not establish an interlocutory relationship, disregarding the dialogical process of language that only has meaning within the text. Therefore, planning differentiated and contextualized literacy strategies for students with intellectual disabilities is a major challenge to teaching practices and actions in the current school configuration, which requires the commitment of everyone involved and more solid special training given the importance and complexity of their work.